2018
DOI: 10.1007/s10856-018-6039-3
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of new materials based on nano-structured nitinol with titanium and tantalum composite surface layers: experimental analysis in vitro and in vivo

Abstract: A technology for obtaining materials from nanostructured nitinol with titanium- or tantalum-enriched surface layers was developed. Surface layers enriched with titanium or tantalum were shown to provide a decrease in the formation of reactive oxygen species and long-lived protein radicals in comparison to untreated nitinol. It was determined that human peripheral vessel myofibroblasts and human bone marrow mesenchymal stromal cells grown on nitinol bases coated with titanium or tantalum-enriched surface layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…Ni ions gradually accumulated in cells also affect the ability of bone morphogenetic protein (BMP-2) to induce alkaline phosphatase (ALP) formation [58,59]. Some studies have shown that compared with Nitinol, the surface layer rich in Ti or Ta can significantly reduce the formation of ROS and longevity protein free radicals [60]. Qiao et al found that among the concentrations of metal ions causing DNA damage in vitro, Cr(III), Fe(II) and Al(III) were 50 μM, while Ni(II) 10uM could cause DNA damage, so different metal ions with the same concentration had different toxic effects on cells [61].…”
Section: Different Metal Ions Can Induce Cell Damagementioning
confidence: 99%
“…Ni ions gradually accumulated in cells also affect the ability of bone morphogenetic protein (BMP-2) to induce alkaline phosphatase (ALP) formation [58,59]. Some studies have shown that compared with Nitinol, the surface layer rich in Ti or Ta can significantly reduce the formation of ROS and longevity protein free radicals [60]. Qiao et al found that among the concentrations of metal ions causing DNA damage in vitro, Cr(III), Fe(II) and Al(III) were 50 μM, while Ni(II) 10uM could cause DNA damage, so different metal ions with the same concentration had different toxic effects on cells [61].…”
Section: Different Metal Ions Can Induce Cell Damagementioning
confidence: 99%
“…The surgery was carried out under Zoletil/xylazine anesthesia (6/12 mg per 1 kg of body weight). The operated animals were sacrificed 60 days after the implantation [25].…”
Section: Implantation Testsmentioning
confidence: 99%
“…Moreover, the toxic properties of nickel and the likelihood of corrosion failure of the material (damage to the product in the environment of operation) limit their applicability [10][11][12][13][14][15][16][17]. The inhibitory effect of nickel ions on cell growth and survival [10,15] and the inflammatory effect of the nickel implant on surrounding tissues [14] have been shown.…”
Section: Introductionmentioning
confidence: 99%